A modelling and simulation framework for the integrated design of aircraft systems. (August 2020) - Cimmino, N; Ponnusamy, SS; Garriga, A Garcia; Mainini, L
New technologies and complex systems are being developed in commercial aviation to meet strict requirements regarding fuel consumption, emissions and noise constraints. This motivates the development of multidisciplinary environments to efficiently manage the increasing complexity of the design process. Under the Clean Sky 2 initiative, the ModellIng and Simulation tools for Systems IntegratiON on Aircraft (MISSION) project aims to develop an integrated framework to holistically support the aircraft design, development and validation processes. Within the MISSION framework, this paper proposes a methodology to handle the integration between the aircraft level and the system level in the early phase of aircraft design. The methodology is demonstrated for the case of the Landing Gear System in the rejected take-off scenario.